Iberian pig production: the problems of success - Daza A.; Olivares A.; Rey A.I.; Ruiz J.; López-Bote C.J. (Mediterranean livestock production: uncertainties and opportunities, 2008)
The Iberian pig constitutes a singular breed, strongly adapted to the ecological conditions of the dehesa ecosystem. This breed includes a number of strains, all of them showing low prolific and growth rates, very early maturing fat deposition, and an excellent meat quality, which is valuated in the market according to the fatty acid profile (palmitic, stearic, oleic and linoleic acids) of subcutaneous fat. This paper mainly deals with available feeding sources of the dehesa for Iberian pigs, the productive features of this breed and the evolution that feeding and production systems have experienced in recent years.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)